Teacher Autonomy And Supervision Of Teacher Performance In Junior High Schools - Farida, Linda Zaenati Nur; Sudana, I Made; Raharjo, Tri Joko (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2023)
This research aims to determine the influence of autonomy and supervision on teacher performance in junior high schools in Ngaliyan sub-district. This type of research is quantitative descriptive research with survey techniques using questionnaires as a data collection method. A questionnaire containing statements regarding research variable indicators, was distributed to 110 teacher respondents in Ngaliyan sub-district junior high schools. The results obtained show that there is a significant influence of teacher work autonomy on teacher performance. Supervision at Ngaliyan Middle School also has a significant effect on teacher performance. Autonomy and supervision influence teacher performance in junior high schools in Ngaliyan subdistrict.